RANCANGAN FLIPPED CLASSROM PADA MATA KULIAH PENELITIAN TINDAKAN KELAS DI ERA NEW NORMAL - Teguh, Teguh; Nizkon, Nizkon; Agusta, Erie (Universitas Esa Unggul, 2021)
AbstractThis research departs from the strategic issue of human and community development in the era of the industrial revolution 4.0 as well as answering the challenges of learning innovation in the new normal era. This era provides a learning challenge based on hybrid learning. This challenge applies to all tertiary institutions, including the Primary School Teacher Education Study Program (PGSD). This urgency is what encourages flipped classron learning research to be carried out as a form of solution to improving the quality of learning based on hybrid learning. The 2019 PKPT findings show that data literacy, professionalism, and pedagogical competencies are competencies needed by teachers in the era of the industrial revolution 4.0. In the 2020 research we want to adopt the findings of the 2019 research into a flipped classroom-based learning design in the Classroom Action Research (CAR) course. Research Stages (1) research and information collection; (2) planning; (3) develop a preliminary form of product; and (4) preliminary filed testing. Research Results (1) flipped classroom-based RAT and SAT modeling in the classroom action research course (product), and (2) the product is suitable for use.Keywords: flipped classroom, hybrid learning, new normal, industrial revolution 4.0AbstrakPenelitian ini berangkat dari isu strategis pembangunan manusia dan masyarakat di era revolusi industri 4.0 sekaligus menjawab tantangan inovasi pembelajran di masa new normal. Era ini memberikan tantangan pembelajaran berbasis hybrid learning. Tantangan ini berlaku untuk semua perguruan tinggi tidak terkecuali Program Studi Pendidikan Guru Sekolah Dasar (PGSD). Urgensi inilah yang mendorong penelitian pembelajaran flipped classron dilakukan sebagai bentuk solusi peningkatan kualitas pembelajaran berbasis hybrid learning. Temuan PKPT 2019 menunjukkan bahwa kompetensi literasi data, profesionalisme, dan pedagogik merupakan kompetensi yang dibutuhkan Guru di era revolusi industri 4.0. Pada penelitian 2020 kami ingin mengadopsi temuan hasil riset 2019 ke dalam desain pembelajaran berbasis flipped classroom pada matakuliah Penelitian Tindakan Kelas (PTK). Tahapan Penelitian (1) research and information collection; (2) planning; (3) develop preliminary form of product; dan (4) preliminary filed testing. Hasil Penelitian (1) permodelan RAT dan SAT berbasis flipped classroom pada mata kuliah penelitian tindakan kelas (produk), dan (2) produk layak digunakan.AbstractThis research departs from the strategic issue of human and community development in the era of the industrial revolution 4.0 as well as answering the challenges of learning innovation in the new normal era. This era provides a learning challenge based on hybrid learning. This challenge applies to all tertiary institutions, including the Primary School Teacher Education Study Program (PGSD). This urgency is what encourages flipped classron learning research to be carried out as a form of solution to improving the quality of learning based on hybrid learning. The 2019 PKPT findings show that data literacy, professionalism, and pedagogical competencies are competencies needed by teachers in the era of the industrial revolution 4.0. In the 2020 research we want to adopt the findings of the 2019 research into a flipped classroom-based learning design in the Classroom Action Research (CAR) course. Research Stages (1) research and information collection; (2) planning; (3) develop a preliminary form of product; and (4) preliminary filed testing. Research Results (1) flipped classroom-based RAT and SAT modeling in the classroom action research course (product), and (2) the product is suitable for use.Keywords: flipped classroom, hybrid learning, new normal, industrial revolution 4.0AbstrakPenelitian ini berangkat dari isu strategis pembangunan manusia dan masyarakat di era revolusi industri 4.0 sekaligus menjawab tantangan inovasi pembelajran di masa new normal. Era ini memberikan tantangan pembelajaran berbasis hybrid learning. Tantangan ini berlaku untuk semua perguruan tinggi tidak terkecuali Program Studi Pendidikan Guru Sekolah Dasar (PGSD). Urgensi inilah yang mendorong penelitian pembelajaran flipped classron dilakukan sebagai bentuk solusi peningkatan kualitas pembelajaran berbasis hybrid learning. Temuan PKPT 2019 menunjukkan bahwa kompetensi literasi data, profesionalisme, dan pedagogik merupakan kompetensi yang dibutuhkan Guru di era revolusi industri 4.0. Pada penelitian 2020 kami ingin mengadopsi temuan hasil riset 2019 ke dalam desain pembelajaran berbasis flipped classroom pada matakuliah Penelitian Tindakan Kelas (PTK). Tahapan Penelitian (1) research and information collection; (2) planning; (3) develop preliminary form of product; dan (4) preliminary filed testing. Hasil Penelitian (1) permodelan RAT dan SAT berbasis flipped classroom pada mata kuliah penelitian tindakan kelas (produk), dan (2) produk layak digunakan.Kata kunci: flipped classroom, hybrid learning, new normal, revolusi industri 4.0Â flipped classroom, hybrid learning, new normal, revolusi industri 4.0